THE COMPOSITION OF VZV INFECTION COMPLICATIONS IN ADULTS AND CHILDREN AND ITS RELATION WITH VZV GENOTYPES - Popov, N. N.; Zaytseva, V. A.; Lyadova, T. I.; Volobueva, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The complications of VZV infection are elucidated in this article; some of them are mentioned in literature only once. The attention was paid to clinical manifestations of them and their features in adults and children. The prevalence of VZV genotypes is highlighted in accordance to scientific available reports. It seems to be important the studying of relations between the virus genotypes and the complications of VZV infection and its prognostic significance for patient cure.